2022
DOI: 10.3390/fishes7050262
|View full text |Cite
|
Sign up to set email alerts
|

Functional Additives as a Boost to Reproductive Performance in Marine Fish: A Review

Abstract: This contribution brings together current knowledge on the use of functional food additives affecting marine fish reproductive performance. This article reviews published studies by several authors who have worked with specialized diets and focused on the dietary needs of brood fish, with the objective of identifying the relevant functional additives with potential to improve reproductive performance. The use of commercial and experimental diets that may have an effect on egg viability, quantity, and quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Moreover, protein and lipid are the main components of egg yolk, which are actively utilized by broodstock as nutrient sources for reproductive development and early embryogenesis [ 11 , 19 ]. Amino acid groups, especially isoleucine, leucine, glutamic acid, valine, alanine, lysine, serine, and aspartic acid, have a significant role in broodstock reproductive development, as reported by previous researchers [ 11 , 15 , 20 , 21 ]. On the other hand, light microscopic observation of ovarian histology indicates the reproductive status and oocyte development stages of broodstock in the reproductive period [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 60%
“…Moreover, protein and lipid are the main components of egg yolk, which are actively utilized by broodstock as nutrient sources for reproductive development and early embryogenesis [ 11 , 19 ]. Amino acid groups, especially isoleucine, leucine, glutamic acid, valine, alanine, lysine, serine, and aspartic acid, have a significant role in broodstock reproductive development, as reported by previous researchers [ 11 , 15 , 20 , 21 ]. On the other hand, light microscopic observation of ovarian histology indicates the reproductive status and oocyte development stages of broodstock in the reproductive period [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 60%
“…On the contrary, Boy et al [15] reported no correlation between fecundity, weight, and length for this species. Fecundity can also be affected by several factors, including environmental sources, nutrition, genetic differences, or a combination of them [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the variation in the gut microbiota structure between fresh/frozen and dry/formulated diets, although fresh/frozen diets are still widely used for reared marine fish in the reproductive phase, where the nutritional requirements remain a challenge [ 58 ]. Some studies have compared the gut bacterial community of wild and farmed marine fish, i.e., live feed vs. formulated commercial feed, and found differences in the bacterial composition [ 54 , 55 , 59 ]; however other environmental factors may explain the observed differences.…”
Section: Discussionmentioning
confidence: 99%